Digital Data-Based Inclusive Vocational Learning Capital in Injection Motor Maintenance Material for Deaf Students - Naufal Irsan Sani Oktalgifari; Iding Tarsidi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Inequality in access to modern technology in vocational education for deaf students is a major obstacle to developing job skills aligned with current industry needs. This study aims to implement and evaluate the effectiveness of digital technology-based vocational learning in Honda injection motor maintenance for deaf students at Special Schools (SLB). The method used is a descriptive qualitative method, involving 2–4 SMALB students as research subjects. Data collection techniques include observing practical activities, documenting, interviewing vocational teachers, and evaluating student skills. A case study was chosen to describe the contextual application of digital technology-based Honda injection engine maintenance learning using K-Line-based OBD FTDI for deaf students in special education units. The learning stages included introduction to tools, demonstrations, data reading practice, diagnosis result interpretation, visual discussions, and basic corrective actions. The results show that students can understand the tools' functions, read fault codes, and visually identify technical problems. Obstacles in understanding technical terms are overcome through visual media-based learning strategies, illustrated guidebooks, and video tutorials. In terms of affection and participation, this learning increases student motivation, confidence, and active involvement in practice. Vocational teachers play a strategic role in simplifying technical concepts into adaptive visual and procedural forms. New findings from this study indicate that the use of digital automotive diagnostic tools as learning media can help bridge the communication barriers faced by deaf students in technical learning contexts. Thus, this approach is considered effective and feasible for continuous integration into the SLB vocational curriculum.